(untitled) (London, 1997)
" ...organisational sensitivity ...will be required to underpin the more fluid, less hierarchical, less functionally oriented internal structures." - Extract from the Management Development to the Millennium Report Creating A Market Sensitive Culture enables you to become more sensitive and responsive when market needs change, so that you can make the right strategic and operational decisions in today's fast moving competitive environment. Authors : Ken Langdon is a consultant and trainer as well as a bestselling author. Andrew Bruce is a management consultant, facilitator and trainer. He also tutors for the Open Business School.
Keywords: Industrial management,Organizational change